In-vitro assessment of crossbred buck fertility - KALE, M M; MANIK, R S; TOMER, O S (The Indian Journal of Animal Sciences, 2013)
A study was conducted on 10 crossbred bucks (aging 2G to 50 months) to evaluate their fertility status on the basis of semen quality and hypo-osmotic swelling test (HOS), cervical mucus penetration test (CMPT) and resistance to 1% NaCI solution during 3 seasons (hot-dry, hot-humid and cold-humid). Collections (150) were made and the quality of semen was evaluated using standard procedures. The analysis of semen revealed that, revealed that, resistance value was significantlyÂ (P<0.01) affected by season. Season, buck and season x buck interaction significantly (P<0.01) influenced HOS-reacted and not-reaeted spermatozoa. Higher resistance value to 1% NaCI solution was obtained during cold-humid season. pH of the cervical mucus had significant (P<0.01) effect on the in vitro penetration rate of goat spermatozoa. HOS test can be used for predicting fertilizing ability of spermatozoa and being simple and rapid, it can be used as a routine assessment technique in laboratories. There is a need to have some criteria for selection of bucks on the basis of semen quality and in vitro assessment of fertility and fertility rate.